Model Predictive Current Control for the Grid‐Connecting Three‐Level NPC Inverters Based on an Effective Harmonic Extraction Method Under a Low‐Switching Frequency. Issue 8 (18th May 2022) - Hou, Wenbao; Tan, Guojun; Li, Delu
Abstract : Current control of the grid‐connecting inverters usually has an important influence on the control performance especially when the inverters operate at a low‐switching frequency for it would result in a severe harmonic distortion in the output current components. To improve the current control performance, a novel model predictive current control (MPCC) strategy based on an effective harmonic extraction method was present for a high‐power three‐level NPC inverter in this paper. First, an effective amplitudes extraction method called generalized sliding discrete Fourier transform (GSDFT) was designed for the fundamental and low‐order harmonic current components, and which would be taken as a part of the cost function for the MPCC besides the consideration of switch losses and neutral point potential balancing issues. Experimental results verify that this kind of novel control strategy not only has a characteristic similar with the selective harmonic elimination, also could realize a nice current control performance even the switching frequency is low than 500 Hz as well as a neutral point potential balancing. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.